To abuse or not to abuse. This is the question. On whether social corporate responsibility influences human rights abuses of large multinational corporations (1990-2006) - Davide Fiaschi; Elisa Giuliani; Chiara Macchi; Michelangelo Murano; Oriana Perrone (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2011)
We are currently observing an apparent paradox. On the one hand there is growing evidence about corporate misbehaviour and Multinational Corporations (MNCs)' violations of human rights. On the other, the largest MNCs are showing an unprecedented level of commitment to save the world through their Corporate Social Responsibility (CSR) initiatives and investments. In this scenario, how much does CSR contribute to curb human rights abuses of the largest worldwide MNCs? This paper investigates this question using a novel dataset of 135 MNCs operating in several sectors over the period 1990-2006. We apply Probit estimations to our data and show that MNCs that have adopted CSR initiatives have higher probabilities of being involved in alleged human rights abuses, but such probability decreases over time, as they accumulate experience in CSR. This result is found for human rights abuses for which MNCs are directly held accountable, whereas our evidence suggests that CSR experience does not curb corporate complicity in abuses committed by third parties. The paper concludes by discussing the normative implications of this result and by suggesting directions for further research.
Keywords: F2; M14; K0; C23; 330; Multinational Corporations (MNCs); Corporate Social Responsibility; Human Rights; Econometrics